2017
DOI: 10.3748/wjg.v23.i15.2640
|View full text |Cite
|
Sign up to set email alerts
|

Is there still a role for the hepatic locoregional treatment of metastatic neuroendocrine tumors in the era of systemic targeted therapies?

Abstract: Gastroenteropancreatic neuroendocrine neoplasms (GEP-NENs) frequently present with distant metastases at the time of diagnosis and the liver is the most frequent site of spreading. The early identification of metastatic disease represents a major prognostic factor for GEP-NENs patients. Radical surgical resection, which is feasible for a minority of patients, is considered the only curative option, while the best management for patients with unresectable liver metastases is still being debated. In the last few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 65 publications
1
18
0
1
Order By: Relevance
“…In our study, the curative effect of LAR and chemotherapy in both PHNETs and metastatic HNETs patients were not specifically evaluated in 81 cases mainly owing to the delayed publication of the above treatment method which makes some of the enrolled patients no objective conditions for accepting LAR or other therapeutic methods, however, the clinical correlation between treatment modalities and survival were explored, we found that, in respect to OS, there was a statistical significance between local/combined treatment modalities and systematic treatment, which indicated that patients who underwent local treatment modality can achieve a better prognosis. Our findings were rightly consistent with the recent analysis 23 .…”
Section: Discussionsupporting
confidence: 94%
“…In our study, the curative effect of LAR and chemotherapy in both PHNETs and metastatic HNETs patients were not specifically evaluated in 81 cases mainly owing to the delayed publication of the above treatment method which makes some of the enrolled patients no objective conditions for accepting LAR or other therapeutic methods, however, the clinical correlation between treatment modalities and survival were explored, we found that, in respect to OS, there was a statistical significance between local/combined treatment modalities and systematic treatment, which indicated that patients who underwent local treatment modality can achieve a better prognosis. Our findings were rightly consistent with the recent analysis 23 .…”
Section: Discussionsupporting
confidence: 94%
“…Комплексное лечение генерализованных НЭО является единственной возможностью оказать реальное влияние на течение заболевания, увеличив продолжительность и качество жизни пациентов, о чем свидетельствуют результаты исследований разных авторов [31]. Так, K. Oberg и соавт.…”
Section: оригинальные статьиunclassified
“…Therefore, it requires a tailored approach that should be shared by a multidisciplinary team including at least medical and radiation oncologists, surgeon, pathologist, endocrinologist, and interventional radiologist. The primary treatment goal should be curative, and radical surgical resection is considered the only curative option, but it can be offered to a minority of patients[ 7 , 11 - 13 ]. Indeed, LM are often present at diagnosis, or occur during the disease, also in slow-growing tumors[ 8 ].…”
Section: Introductionmentioning
confidence: 99%